RUMAH BIBIT HORTUKULTURA SEBAGAI SOLUSI KETAHANAN PANGAN KELUARGA DI DESA SAMA GUNA KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA NUSA TENGGARA BARAT - Aryana, I Gusti Putu Muliarta; Alfitmatun, Alfitmatun; Putri, Aulia Shara; Khilafatulqudduus, Ghalby; Nensi, Baiq Arya; Ramdani, Wahyu; Astarina, Raditia; Kumairah, Titi; Agustina, Agustina; Puspitasari, Apin; Wikanto, Aditya Kusuma (Jurnal Wicara, 2023)
The construction of seed houses is a solution to meet family food needs. Nurseries are a way of implementing sustainable agriculture, nurseries are made so that seed germination can take place under controlled climatic conditions. This is necessary for plant growth, namely by paying attention to temperature, calculating light transmission and adjusting air humidity evenly according to plant needs. The problem experienced by most people is the lack of supply of ready-to-plant seeds. Therefore, the aim of this activity is the formation of quality horticultural seed houses and seeds, namely chilies, mustard greens and kale. The method of implementing the activity is carried out in 3 stages, namely site surveys, outreach and building seedling houses as well as planting and caring for seedlings. The results of the activity show that a horticultural nursery has been formed and the results of chili, mustard and kale nurseries that can meet the community's supply needs for better quality horticultural seeds.